High temperature mechanical integrity of selective laser melted alloy 718 evaluated by slow strain rate tests. (May 2021) - Deng, Dunyong; Peng, Ru Lin; Moverare, Johan
Abstract: Strain rate dependent deformation behaviours of selective laser melted Alloy 718 (IN718) are systematically studied at 550 and 650 °C by slow strain rate testing, with a forged counterpart as a reference. Selective laser melted IN718 shows significant susceptibility to intergranular cavitation, resulting in ductility degradation with decreasing strain rate. Detailed fractography and cross section inspections are employed to identify the damage mechanisms. Creep rates are also estimated and compared with the conventional counterparts. The possible critical factors for the inferiority of time dependent damage resistance of selective laser melted IN718 are discussed. Highlights: Strain rate dependent deformation of SLM IN718 was studied at 550 and 650 °C, with a forged counterpart as reference. Effects of intragranular deformation, creep and environmental embrittlement on fracture were correlated with strain rates. Ductile intergranular premature fracture at extremely limited elongation was observed for SLM IN718. Rapid formation of GB cavities by stress-assisted diffusion was the principal factor for inferior ductility of SLM IN718.